General idea of application system for space-ground integrated information network - Chunting WANG; Lijun ZHAI; Ning LI; Ningning LU (Dianxin kexue)
The space-ground integrated information network can offer global coverage by connected air,ocean and land networks with hybrid orbit satellite constellation.This infrastructure can provide a new solution for applications of marine,aviation,aerospace,inclusive information system and global commercial broadband communication.It can also support the implementation of national strategies such as B＆amp;R with communication applications.On the basis of fully drawing on international advanced technology,industry and application service experience,through the development of a typical application demonstration system,the capability of the world-wide integrated information network was verified and more application requirements and business models were drawn.And some preliminary considerations and ideas were put forward for the construction of a typical application system of the space-ground integrated information network in the future,providing basic public services and professional services to all kinds of users worldwide.